Intercultural Communication Between Arab And Betawi Communities In Condet In Maintaining Social Harmony - Fitri Chairani; Shafa Aulia Rahma; Az Zahra Nasywa Usmadi; Riana Marciela; Risca Adelia Putri; Meranti (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Condet, located in East Jakarta, is a multicultural area inhabited by Betawi communities and Arab descendants who have coexisted for generations. This study aims to examine how intercultural interaction and communication between Arab and Betawi communities in Condet contribute to the maintenance of social harmony amid cultural diversity and ongoing social change. Using a qualitative approach with a constructivist paradigm, this research employs field research methods through observations, in-depth interviews, and literature review. Data were collected from community leaders, religious figures, local business actors, and residents actively involved in social and religious activities. The findings reveal that social harmony in Condet is shaped by a long historical process of coexistence, strong religious values as a shared social foundation, effective everyday communication, and cultural integration through intermarriage and economic cooperation. Social interactions occur naturally without rigid ethnic boundaries, supported by shared language use and collective religious practices. Although challenges such as modernization, declining traditional social activities, and external influences exist, these issues have not led to significant conflict. Instead, they are generally resolved through open communication and communal deliberation. This study concludes that effective intercultural communication and shared social values play a crucial role in sustaining harmony in multicultural urban communities, positioning Condet as a relevant model for peaceful interethnic coexistence.